1983
DOI: 10.1038/bjc.1983.153
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the pharmacokinetic properties of nimorazole

Abstract: The pharmacokinetics of the hypoxic radio-sensitizer nimorazole were studied in 19 individuals after single oral doses of between 0.5-3.5 g. HPLC measurements showed, after a rapid absorption, a linear relationship between peak plasma concentration and given dose. Mean elimination half life was 3.1 h. A tendency to a dose-dependent variation in the apparent volume of distribution, total body clearance and elimination half life suggest non-linear pharmacokinetics of nimorazole. Tumour concentrations measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Measurement of drug concentrations.-Blood samples were obtained by open-heart puncture after killing the mice by cervical dislocation, Plasma concentrations were measured by reversed-phase high-pressure liquid chromatography (HPLC) (Overgaard et al, 1983) by injecting 25 ,lI of the sample in a nucleosil 10 Fm C18 column at a flow of 2 ml/min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurement of drug concentrations.-Blood samples were obtained by open-heart puncture after killing the mice by cervical dislocation, Plasma concentrations were measured by reversed-phase high-pressure liquid chromatography (HPLC) (Overgaard et al, 1983) by injecting 25 ,lI of the sample in a nucleosil 10 Fm C18 column at a flow of 2 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, comparable data indicate that nimorazole has considerably less acute or chronic toxicity in dogs, and nimorazole seems to be even less toxic in dogs than metronidazole (Roche, unpub-lished data; Farmltalia, Carlo Erba, unpublished data). In humans nimorazole has been given in doses up to 25 g in 10 days without causing peripheral neuropathy or other severe side effects (Overgaard et al, 1983). Thus nimorazole seems to be considerably better tolerated than MISO, and on the basis of largeanimal toxicity it may be tolerated as well as metronidazole (Flagyl) which can be given in daily doses of 6 g/m2 and in total doses up to 100 g (Kapp et al, 1982;Karim, 1978;Urtasun et al, 1975).…”
Section: I)iscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that the combined DOX and photothermal treatments were more cytotoxic than chemotherapy or photothermal treatment alone. This synergistic effect was probably ascribed to enhanced cytotoxicity of DOX at elevated temperatures [18][19][20] and a higher heat sensitivity for the cells exposed to DOX than for the cells not exposed to DOX. [ 12 ] During the treatments, we also measured the body weight of the mice, since high toxicity usually leads to weight loss.…”
mentioning
confidence: 99%